From Evidence to Impact: Recommendations for a Dissemination Support System. Issue 149 (September 2015) - Kreuter, Matthew W.; Wang, Monica L.
Abstract: While finding effective solutions to child and adolescent health problems is very much a scientific endeavor, getting those solutions into widespread practice largely is not. This paper applies lessons from business and engineering to highlight the shortcomings of current approaches to science translation. In challenging the status quo, the paper introduces and defends three propositions: that many evidence‐based programs are not worth disseminating; most research‐tested versions of programs are not ready for widespread use; and most intervention developers and testers make poor disseminators. These propositions provide the basis for recommending three components of an enhanced dissemination support system, and the conceptualization of a new model to disseminate evidence‐based solutions to promote child and adolescent health. © 2015 Wiley Periodicals, Inc.